Mourning Philology : Art and Religion at the Margins of the Ottoman Empire - Nichanian, Marc, 1946- (Book collections on Project MUSE., 2014)
'Mourning Philology' proposes a history of the 19th century national imagination as a reaction to the two main philological inventions of that century: 'mythological religion' and the 'native'. This history is illustrated with the case of the Armenians in the Ottoman Empire. The book offers an account of the successive stages (archeological, self-ethnographic, and aesthetical) of the implementation of orientalist philology, through which the nation came to existence. It is also part of a general reflection on the nature of the Catastrophe and the way it destroys the possibility of mourning.